2001
DOI: 10.4049/jimmunol.166.4.2235
|View full text |Cite
|
Sign up to set email alerts
|

Novel Secondary Ig VH Gene Rearrangement and In-Frame Ig Heavy Chain Complementarity-Determining Region III Insertion/Deletion Variants in De Novo Follicular Lymphoma

Abstract: Human germinal center B cell tumors retain the ability of their nontransformed counterparts to somatically hypermutate Ig V genes by nucleotide substitution. Among a survey of 60 primary previously untreated, clonal, follicular lymphomas we have identified a rare VH rearrangement variant and two other in-frame nucleotide insertion/deletion variants within complementarity-determining region III of the Ig heavy chain. The neoplastic origin of the VH rearrangement variant was directly demonstrated in cells isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Reversion of the V gene shows that not all of the antibody maturation is required for neutralization of select isolates. It remains to be seen whether the long CDR H3 is a product of affinity maturation (growing like a pedunculated tumor from the combining site), or if a rare natural process allows it to spring fully formed from the combining loops as has been shown previously in other cases (25). Domain swapping to enhance functional resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Reversion of the V gene shows that not all of the antibody maturation is required for neutralization of select isolates. It remains to be seen whether the long CDR H3 is a product of affinity maturation (growing like a pedunculated tumor from the combining site), or if a rare natural process allows it to spring fully formed from the combining loops as has been shown previously in other cases (25). Domain swapping to enhance functional resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these IgD + CD27 + memory B cells could be selectively derived from a more restricted naïve B cell population that harbored shorter CDR3 regions than did the circulating naïve B cells or IgD − CD27 + memory B cells. Interestingly, studies of germinal center human tonsilar B cells, follicular lymphoma cells or synovial B cells in rheumatoid arthritis patients have demonstrated that the progress of somatic hypermutation could introduce insertions and deletions into CDR regions of immunoglobulin V genes in addition to base-pair substitutions, although at a very low frequency (Kobrin et al, 2001;Wilson et al, 1998). It is possible that the unique features we observed in the profile of junctional nucleotide insertions and deletions of V H genes for IgD + CD27 + memory B cells were due partially to a lower frequency of somatic hypermutation events that occurred during the affinity maturation of these memory B cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is one concern about these sequences. On their own, they are too short at the 3' end for recognition of a J H segment but nt 303-328 are identical to nt 302-327 of ST1R M26, M10, M6, and M31 ( (Choi et al 1996;Kobrin et al 2001;Rosenquist et al 1999;Steenbergen et al 1993;Steenbergen et al 1996;Steenbergen et al 1997;Wasserman et al 1992 The finding that the sequences described here could be explained by gene conversion suggests that other cases of Type 2 V H replacement in Man might also be examples of the same process but are not recognised because the 5' end of the converted section is upstream of the beginning of the sequenced region ( Fig. 4b(ii)).…”
Section: Discussionmentioning
confidence: 99%